(untitled) (Journal of the College of Basic Education, 2023)
The aim of this work is to introduce new definition of fuzzy pre-Hilbert space (fuzzy inner product space) and discussed the relation between fuzzy pre-Hilbert space and ordinary pre-Hilbert space. Much attention is paid to the concepts of convergence of sequence (for example Cauchy sequence of fuzzy point) and the concept of boundness of these sequences.